Chapter - 5, Functions

Section - 5.4 - Images and Inverse Images: A Research Project


Summary

  • Suppose $f : A → B$ and $X \subseteq A$. Then the image of $X$ under $f$ is the set $f(X)$ defined as follows:
    $f(X) = \{ f(x) \, \vert \, x \in X \} = \{ b \in B \, \vert \, \exists x \in X ( f(x) = b) \}$.
  • If $Y \subseteq B$, then the inverse image of $Y$ under $f$ is the set $f^{−1}(Y)$ defined as follows:
    $f^{−1}(Y ) = \{ a \in A \, \vert \, f(a) \in Y \}$.
  • In this section, we also learned a way to come up with counter examples. It might not help always for finding counter examples but it may atleast give a starting point. The outline is as follows:
    • Try to prove the theorem.
    • If theorem is not correct, we will get stuck at some point.
    • Try to use the information gathered from the point where we are stuck in the proof to come up with counter example.

Soln1

(a)

Yes it will always be true. Proof:

($\to$)Suppose $y \in f(W \cup X)$. Thus for some $x \in W \cup X$, $f(x) = y$. Thus we have two cases:

Case 1: $x \in X$
Thus $y = f(x)$ and $x \in X$, it follows $y \in f(X)$. Or we can also say $y \in (f(X) \cup f(W))$.

Case 2: $x \in W$
Thus $y = f(x)$ and $x \in W$, it follows $y \in f(W)$. Or we can also say $y \in (f(X) \cup f(W))$.

Thus from both cases, $y \in (f(X) \cup f(W))$. Since $y$ is arbitrary, it follows that $f(W \cup X) \; \subseteq \; f(W) \cup f(X)$.

($\rightarrow$) Suppose $y \in f(W) \cup f(X)$. Thus we have two possible cases:

Case 1: $y \in f(W)$.
Thus for some $x \in W$, $f(x) = y$. Since $x \in W$, it follows $x \in W \cup X$. Since $x \in W \cup X$ and $f(x) = y$, it follows $y \in f(W \cup X)$.

Case 2: $y \in f(X)$.
Thus for some $x \in X$, $f(x) = y$. Since $x \in X$, it follows $x \in W \cup X$. Since $x \in W \cup X$ and $f(x) = y$, it follows $y \in f(W \cup X)$.

Thus from both cases $y \in f(W \cup X)$. Since $y$ is arbitrary, it follows that $f(W) \cup f(X) \; \subseteq \; f(W \cup X)$.

Since $f(W \cup X) \; \subseteq \; f(W) \cup f(X)$ and $f(W) \cup f(X) \; \subseteq \; f(W \cup X)$, it follows that $f(W \cup X) \; = \; f(W) \cup f(X)$.

(b)

No, it is not true. Counter example:

Suppose $f = \{ (1,a), (2,b), (3,a) \}$.
$W = \{1, 2\}, X = \{ 2, 3\}$.

Thus, $f(W) = \{ a,b\}$.
$f(X) = \{b,a\}$.
$f(W) \setminus f(X) = \phi$.

Also, $W \setminus X = \{1 \}$, Thus $f(W \setminus X) = \{a\}$.

Clearly $f(W \setminus X) \; \ne \; f(W) \setminus f(X)$.

(c)

No, it is not true. Counter example:

Note: Earlier solution was wrong. Check the comments.

Updated Solution:

Suppose $f = \{ (1,a), (2,b), (3,a) \}$.
$W = \{1\}, X = \{2, 3\}$.

Clearly $W \nsubseteq X$.

Now, $f(W) = \{a\}$ and $f(X) = \{a, b\}$. Clearly $f(W) \subseteq f(X)$ but $W \nsubseteq X$.

Old(Wrong) Solution:

Suppose $f = \{ (1,a), (2,b) \}$.
$W = \{1\}, X = \{ 1, 2\}$.

Clearly $W \subseteq X$.

Now, $f(W) = \{a\}$ and $f(X) = \{a, b\}$. Clearly $f(W) \nsubseteq f(X)$. Thus $W \subseteq X$ but $f(W) \nsubseteq f(X)$.


Soln2

(a)

Yes, it will be always true. Proof:

($\to$)Suppose $x \in f^{-1}(Y \cap Z)$. Thus $x \in A$ and $f(x) \in Y \land f(x) \in Z$. Since $x \in A$ and $f(x) \in Y$, it follows $x \in f^{-1}(Y)$. Similarly, since $x \in A$ and $f(x) \in Z$, it follows $x \in f^{-1}(Z)$. Thus $x \in f^{-1}(Y) \cap f^{-1}(Z)$. Since $x$ is arbitrary, it follows $f^{-1}(Y \cap Z) \; \subseteq \; f^{-1}(Y) \cap f^{-1}(Z)$.

($\leftarrow$)Suppose $x \in f^{-1}(Y) \cap f^{-1}(Z)$. Thus $x \in f^{-1}(Y)$ and $x \in f^{-1}(Z)$. It follows that $x \in A$ and $f(x) \in Y$ and $f(x) \in Z$. It follows $f(x) \in Y \cap Z$. Since $x \in A$ and $f(x) \in Y \cap Z$, it follows that $x \in f^{-1}(Y \cap Z)$. Since $x$ is arbitrary, it follows $f^{-1}(Y) \cap f^{-1}(Z) \; \subseteq \; f^{-1}(Y \cap Z)$.

Thus from both directions, we can conclude $f^{-1}(Y \cap Z) \; = \; f^{-1}(Y) \cap f^{-1}(Z)$

(b)

Yes, it will be always true. Proof:

($\to$)Suppose $x \in f^{-1}(Y \cup Z)$. Thus $x \in A$ and f(x) \in Y \lor f(x) \in Z $$. Thus we have two cases:

Case 1: $f(x) \in Y$
Since $x \in A$ and $f(x) \in Y$, it follows $x \in f^{-1}(Y)$.

Case 2: $f(x) \in Z$
Since $x \in A$ and $f(x) \in Z$, it follows $x \in f^{-1}(Z)$.

Thus we have $x \in f^{-1}(Y)$ or $x \in f^{-1}(Z)$. It follows $x \in f^{-1}(Y) \cup f^{-1}(Z)$.

Since $x$ is arbitrary, it follows $f^{-1}(Y \cup Z) \; \subseteq \; f^{-1}(Y) \cup f^{-1}(Z)$.

($\leftarrow$)Suppose $x \in f^{-1}(Y) \cup f^{-1}(Z)$. Thus $x \in f^{-1}(Y)$ or $x \in f^{-1}(Z)$. It follows we have following cases:

Case 1: $x \in f^{-1}(Y)$
Thus $x \in A$ and $f(x) \in Y$. Or we can also say $f(x) \in Y \cup Z$.

Case 2: $x \in f^{-1}(Z)$
Thus $x \in A$ and $f(x) \in Z$. Or we can also say $f(x) \in Y \cup Z$.

It follows from all possible cases that $x \in A$ and $f(x) \in Y \cup Z$. Thus $x \in f^{-1}(Y \cup Z)$. Since $x$ is arbitrary, it follows that $f^{-1}(Y) \cup f^{-1}(Z) \; \subseteq \; f^{-1}(Y \cup Z)$.

Thus we have $f^{-1}(Y \cup Z) \; \subseteq \; f^{-1}(Y) \cup f^{-1}(Z)$ and $f^{-1}(Y) \cup f^{-1}(Z) \; \subseteq \; f^{-1}(Y \cup Z)$. We can conclude that $f^{-1}(Y \cup Z) \; = \; f^{-1}(Y) \cup f^{-1}(Z)$.

(c)

Yes, it will be always true. Proof:

($\to$)Suppose $x \in f^{-1}(Y \setminus Z)$. Thus $x \in A$ and $f(x) \in Y \setminus Z$. Thus $f(x) \in Y \land f(x) \notin Z$. Since $x \in A$ and $f(x) \in Y$, it follows $x \in f^{-1}(Y)$. Also, since $x \in A$ and $f(x) \notin Z$, it follows $x \notin f^{-1}(Z)$. Since $x \in f^{-1}(Y)$ and $x \notin f^{-1}(Z)$, it follows that $x \in f^{-1}(Y) \setminus f^{-1}(Z)$. Since $x$ is arbitrary, it follows $f^{-1}(Y \setminus Z) \; \subseteq \; f^{-1}(Y) \setminus f^{-1}(Z)$.

($\leftarrow$)Suppose $x \in f^{-1}(Y) \setminus f^{-1}(Z)$. Thus $x \in f^{-1}(Y)$ and $x \notin f^{-1}(Z)$. Since $x \in f^{-1}(Y)$, it follows $x \in A$ and $f(x) \in Y$. Since $x \in A$ and $x \notin f^{-1}(Z)$, it follows $f(x) \notin Z$. Thus we have $f(x) \in Y$ and $f(x) \notin Z$. It follows $f(x) \in Y \setminus Z$. Since $x \in A$ and $f(x) \in Y \setminus Z$, it follows that $x \in f^{-1}(Y \setminus Z)$. Since $x$ is arbitrary, it follows that $f^{-1}(Y) \setminus f^{-1}(Z) \; \subseteq \; f^{-1}(Y \setminus Z)$.

Now we can conclude from both directions that $f^{-1}(Y \setminus Z) \; = \; f^{-1}(Y) \setminus f^{-1}(Z)$.

(d)

No, it is not always true. Counter example:

Suppose $A=\{a,b\}, B = \{1,2,3\}, Y = \{1\}, Z = \{1,2\}, f = \{(a,1), (b,3) \}$.

Thus $Y \subseteq Z$.

Also, $f^{-1}(Y) = \{a\}$ and $f^{-1}(Z) = \{a\}$. Thus $f^{-1}(Y) \subseteq f^{-1}(Z)$.

Thus even if $f^{-1}(Y) \subseteq f^{-1}(Z)$, $Y \nsubseteq Z$.


Soln3 False.

Suppose $A = \{1,2,3\}, X = \{1,3\}, f = \{(1,a), (2,a), (3,b) \}$.

Thus $f(X) = \{a,b\}$ and $f^{-1}(f(X)) = \{1,2,3\}$. Thus $f^{-1}(f(X)) \ne X$. Thus if $f$ is not one-to-one, theorem is not correct.


Soln4 False.

Suppose $A=\{a,b\}, B = \{1,2,3\}, Y = \{1\}, Z = \{1,2\}, f = \{(a,1), (b,3) \}$.

Also, $f^{-1}(Y) = \{a\}$ and $f(f^{-1}(Y)) = \{1,3\}$. Thus $f(f^{-1}(Y)) = \{1,3\} \ne Y$. Thus if $f$ is not onto, theorem is incorrect.


Soln5 TODO


Soln6

Suppose $P$ denotes inverse image of $Y$ under $f$. Thus $P = \{ a \in A \, \vert \, f(a) \in Y \}$.

Also suppose $Q$ denotes image of $Y$ under $f^{-1}$. Thus $Q = \{ a \in A \, \vert \, \exists y \in Y(f^{-1}(y) = a) \}$.

($\to$)Suppose $x \in P$. Thus $x \in A$ and $f(x) \in Y$. Suppose $y = f(x)$. Thus $y \in Y$ and $f^{-1}(y) = x$. Thus there exists an element $y \in Y$ such that $f^{-1}(y) = x$. It follows that $x \in Q$. Thus $P \subseteq Q$.

($\leftarrow$)Suppose $x \in Q$. Thus for some element $y \in Y$ we have $f^{-1}(y) = x$. Since $f$ is one-to-one and onto, and $f^{-1}(y) = x$, it follows $f(x) = y$. Since $x \in Q$, it follows $x \in A$. Since $x \in A$ and $f(x) = y \in Y$, it follows $x \in P$. Thus $Q \subseteq P$.

Since $P \subseteq Q$ and $Q \subseteq P$, we can conclude that $P = Q$.